EVALUASI DAN REFORMULASI STRATEGI PROMOSI FESTIVAL PARADE PESONA KEBANGSAAN KABUPATEN ENDE, NUSA TENGGARA TIMUR - Aloysius P. Langga B.T. (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2019)
The implementation of the tourism festival event is one way to promote tourism potential. In addition to the purpose of tourism promotion, the festival is held to increase the number of tourist visits, increase local revenue, and provide economic income for the local community. Since 2015, the Ende Regency government through the Tourism Office has conducted a tourism event. The event was the “Festival Parade Pesona Kebangsaan (FPPK)”. This festival has aims to promote tourist attraction objects in Ende Regency as well as to commemorate the history of the birth of Pancasila which was sparked by Bung Karno during his exile in Ende (1934-1938). “Festival Parade Pesona Kebangsaan” is not yet perfect and still needs a lot of improvement. The implementation of promotional activities and tourism promotion is also still limited to the implementation of formalities and without good preparation. The focus of this research is the evaluation and reformulation of the promotion strategy of the “Festival Parade Pesona Kebangsaan” in Ende Regency, which is divided into the identification and analysis of the factors that influence the activities of the “Festival Parade Pesona Kebangsaan”, as well as the evaluation and reformulation of the promotion strategy to perfect the next program of activities. This study uses a descriptive-analytic method with a qualitative approach that aims to describe and evaluate and reformulate the promotion strategy of the “Festival Parade Pesona Kebangsaan” in Ende.